2014
DOI: 10.1007/s00276-014-1267-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of CBCT to investigate the root canal morphology of mandibular incisors

Abstract: Routine mode CBCT imaging was clinically useful for detection of two canals and determines the position of root canal bifurcations in mandibular incisors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
60
7
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 23 publications
10
60
7
12
Order By: Relevance
“…15 Although the rates of bilateral double root canal were relatively lower in the present study, the finding that the bilateral double root canal was seen more in the incisors is similar. In another study conducted on mandibular incisors, overall symmetry in the root canal numbers was found in 94-95% of the cases, 11 compared to 90-95% in the current study (Table 3).…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…15 Although the rates of bilateral double root canal were relatively lower in the present study, the finding that the bilateral double root canal was seen more in the incisors is similar. In another study conducted on mandibular incisors, overall symmetry in the root canal numbers was found in 94-95% of the cases, 11 compared to 90-95% in the current study (Table 3).…”
Section: Discussionmentioning
confidence: 78%
“…This finding is quite similar to that of a previous Turkish study, 21 although other studies have reported a statistically significant difference between genders for the incisors. 11,23 Age displayed an inverse relationship with the frequency of two root canals, probably due to the deposition of secondary dentin in the root canal, which may ultimately result in obliteration of the root canal space. In support of this possibility, a previous study of the maxillary incisors found that the root canal space decreases with increasing age, 28 and that the middle mesial root canal in mandibular molars is less frequently seen in older patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations